Challenges for central banking - Viotti, Staffan; Santomero, Anthony M.; Vredin, Anders (Boston : Kluwer Academic, 2010)
This volume offers a comprehensive examination of what central banks have done, what they can do, and what they should and should not do. The essays provide analyses of the key issues facing central banks at the dawn of the 21st century.
Includes bibliographical references and index.
oif 16/06/15; nmn 20/02/17
Loan
Keywords: Banks and banking, Central